Conceptual Models for Development of Universities in Russia - Tatyana Maximova; Irina Sokolova; Dmitry Verzilin; Tatyana Kruglova (Communications of International Proceedings, 2020)
In the last decade, scientific activities of large universities in Russia have been actively funded by the state. Universities are making attempts to implement one or several development models at once: a research university, a world-class university, an entrepreneurial university, a flagship university of the region, etc. The lack of a clear understanding of the strategy and model of the development of the university can lead to the formal fulfillment of the efficiency indicators set by the state and low real efficiency of spending budget funds. A statistical study for open data of annual monitoring of the Russian universities let determine and analyze the models of the activities of Russian universities in the field of scientific research and innovative developments have been determined. The universities were identified that implement promising, from the point of view of world experience, models of scientific management. Differences in the development of the field of research and development in national research universities were revealed. It was shown that an increase in the share of extra-budgetary funds and in the share of funds of universities for research and development is not accompanied by an increase in the effectiveness of innovative activities in the regions. The performed classification of regions and the calculated values of the factors of the innovative activity efficiency and the financial conditions for the operation of regional flagship universities can be used to plan further support for flagship universities at the expense of the federal budget.
Keywords: Flagship University; Innovative Regional Development; National Research Universities.